2018
DOI: 10.1007/s12017-018-8512-z
|View full text |Cite
|
Sign up to set email alerts
|

The FOXP3 rs3761547 Gene Polymorphism in Multiple Sclerosis as a Male-Specific Risk Factor

Abstract: The FOXP3 gene encodes a transcription factor and is predominantly expressed in the CD4+CD25+ regulatory T cells which plays a pivotal role in the maintenance of immune homeostasis. The defect of FOXP3 gene may provide a critical link between autoimmunity and immune deficiency. The purpose of our study was to evaluate the association of chosen polymorphisms of FOXP3 gene (rs3761549, rs3761548, rs3761547) with different clinical multiple sclerosis (MS) data of our relapsing-remitting groups of patients and in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…A study from Poland found no association between rs3761548 and rs3761549 gene polymorphisms and multiple sclerosis (MS) [ 48 ]. The same result was concluded in the Slovak population for rs3761548 [ 17 ] and also from the genome-wide association study (GWAS) on the Caucasian population [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Poland found no association between rs3761548 and rs3761549 gene polymorphisms and multiple sclerosis (MS) [ 48 ]. The same result was concluded in the Slovak population for rs3761548 [ 17 ] and also from the genome-wide association study (GWAS) on the Caucasian population [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jafarzadeh et al [ 42 ] and Eftekharian et al [ 43 ] found an association between rs3761548 FOXP3 gene and MS in an Iranian population. Recently, Wawrusiewicz-Kurylonek et al [ 24 ] investigated the association of three SNPs of FOXP3, including the rs3761548 and the rs3761547, on MS risk in a Polish population. The authors found a gender-specific relation between rs3761547 FOXP3 gene polymorphism and MS susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…We selected two SNPs in the FOXP3 gene, namely rs3761548 and rs3761547, and a SNP in the GATA3 gene, namely rs3824662, based on evidence in the literature [ 23 , 24 ]. Characteristics of all selected SNPs are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The suppressor function of Treg cells could be impaired due to the deficiency of the FOXP3 gene. Many studies have reported that FOXP3 gene single nucleotide polymorphisms (SNPs), particularly the regulatory polymorphisms located in the promoter regions, are associated with several autoimmune diseases, such as allergic rhinitis, type I diabetes (TID), systemic lupus erythematosus (SLE), multiple sclerosis (MS), and autoimmune thyroid diseases (AITD) 12‐16 . Three loci −6054 del/ATT (rs5902434), −3279 A/C (rs3761548), and −924 A/G (rs2232365) are located in or near the transcription initiation and cis‐acting elements of FOXP3 gene.…”
Section: Introductionmentioning
confidence: 99%